Atendimento educacional especializado na educação infantil : interface com os pais e professores da classe comum - Rodrigues, Roberta Karoline Gonçalves (2015)
The education in regular classrooms for students that are special education's target group in the early childhood education creates the need of diversified services to overcome some of the difficulties that may appear. One of this services is the Specialized Educational Services (SES) that has to be offered to them, preferably, in the Multifunctional Resource Classrooms (MRC). This service must be iniciated in the age group of zero to six years olg, be offered in public schools or in specialized educational's institutes and reckon with parents and teacher's participation. Considering the importance of this service, principally related to this age group, and the recent implementation of it, this study justifies in the search to comprehend how it happens and how it's the participation of the people involved in this proccess, like parents and teachers. Based on that, the main objective of this study was to describe and analyse how this specialized educational services in the multifunctional resource classrooms for preschoolers happens and the participation of parents and regular teachers in this proccess. There were a total of 20 participants being, two teachers that worked in MRC in the early childhood education, six children (being three children to each teacherd) that attended the SES in the MRC, their parents and regular teaches. The study happened in a daycare and four municipal preschools, located in a city of São Paulo. Data were collected through three interviews guides: (a) one to the MRC teachers; (b0 one to the regular teachers and (c)one to the parents. Besides, were made seven observation's session for each student, and they all followed an observation protocol, with the objective to follow the service ad identify the practices used. Data were analysed through content analyses with the qualitative data that were obtained with the interviews and the data collected through observation were analysed in categories. it was possible to verify, using case studies, that the majority of parents were satisfied with the work that was being developed with their child, even though the articulation between parents and SES teachers and regular teachers almost did not exist. In relation to the regular teachers, it was possible to verify that the majority believed that the students that were special educations' target group have had gotten improvements in their classrooms. Just one teacher used to keep in touch with the MRC teacher, even though all of them believed that this kind of contact was essencial, wich mean that they did not have any kind of colaboration between them. Even with the lack of knowledge about the work developed in the SES, they used to believe that the improvement in their students happened because they had access to this kind of services. SES teachers did not keep in touch with any other professional to exchange experiences. The contact with regular teachers used to happen by email or reunions, even though this kind of contact was rare. The contact with parents happened every time their child went to SES, but they were not allowed to participate of them. Some strategies used by both teachers were highlighted like the time dedicated to free play and the use of the child's name as a start to their literacy, besides the priorization of the use of games in their practice.